Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-97358-5
|View full text |Cite
|
Sign up to set email alerts
|

The fatty degeneration of the lumbar erector spinae muscles affects dynamic spinal compensation ability during gait in adult spinal deformity

Abstract: This study aimed to investigate whether fat infiltration in lumbar paravertebral muscles assessed by magnetic resonance imaging (MRI) could be related to dynamic sagittal spino-pelvic balance during gait in adult spinal deformity (ASD). This is a retrospective analysis of 28 patients with ASD. The fat infiltration rate of lumbar erector spinae muscles, multifidus muscles and psoas major muscles was measured by T2 weighted axial MRI at L1-2 and L4-5. Dynamic sagittal spinal and pelvic angles during gait were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In previous studies, gait analysis has been performed on relatively short distance walking [ 10 , 11 , 17 19 ] or comparing the walking posture between the initiation and cessation of gait [ 9 , 12 , 14 , 15 ]. These studies reported that the spinal balance during gait was leaning forward, even in the healthy group [ 18 ]; however, the difference from the upright position was significantly larger in the ASD group [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, gait analysis has been performed on relatively short distance walking [ 10 , 11 , 17 19 ] or comparing the walking posture between the initiation and cessation of gait [ 9 , 12 , 14 , 15 ]. These studies reported that the spinal balance during gait was leaning forward, even in the healthy group [ 18 ]; however, the difference from the upright position was significantly larger in the ASD group [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our hypothesis, no response to increased spinal alignment was evident in the muscle activity of the lumbar PVM. Lower lumbar muscle degeneration is more severe in ASD [ 12 , 24 ]. The activity of the lumbar PVM might have reflected its fatty infiltration due to severe degeneration, causing the per unit muscle volume measured by surface EMG to be less than the thoracic PVM and Quad.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Again, only LuM MFI (not fibrosis) would explain the positive relationship with ECHO LuM , as an increased MFI in the posterior vertebral muscles (erector spinae + LuM) has been associated with pelvic retroversion (Elysee et al, 2021;Lee et al, 2022;Zhang et al, 2021). However, MFI in LuM was not enough to induce a change in pelvic inclination in 93 healthy controls (Menezes-Reis et al, 2018), which was later confirmed in a study showing a relationship with the erector spinae MFI but not LuM MFI in participants with spinal deformity (Miura et al, 2021). This could suggest that the participants of the present study may also have erector spinae MFI.…”
Section: Barrierssesmentioning
confidence: 92%